Modeling of Supplier Selection Strategy And Raw Material Order Allocation With Analytic Hierarchy Process Approach and Linear Programming at PT. IKSG - Zulaihan, Ahmad; Siswanto, Nurhadi (Eduvest - Journal of Universal Studies, 2025)
The dynamics and challenges of the business environment require companies to adapt quickly and responsively to changes. The ability to meet customer expectations through quality products and services at competitive prices is the key to the company’s sustainability. A reliable supply chain plays an important role in this matter, not only ensuring economic efficiency, but also paying attention to social and environmental aspects. Trusted suppliers are the main support to ensure the availability of quality raw materials, competitive costs, and are supported by good after-sales service. This research aims to develop an integrated model to overcome the problem of supplier selection and raw material order allocation at PT. IKSG. The model combines the Analytic Hierarchy Process (AHP) and Linear Programming approaches. AHP is used to objectively evaluate and determine the best supplier selection, while Linear Programming allocates the optimal order quantity to each of the selected suppliers. The study’s results successfully identified the criteria for selecting suppliers that support the concept of sustainability. The three main criteria obtained were economic (weight 63.16%), environment (weight 26.67%), and social (weight 10.17%). Economic criteria have subcriteria of quality, cost, availability, flexibility, delivery, and finance. Environmental criteria have subcriteria for waste management, reputation, and environment-related certificates. Social criteria have subcriteria for the rights of employees, working hours, and worker safety. From the evaluation of six alternative suppliers, the three best suppliers were selected. The optimal allocation of raw material orders is allocated to SDP (S1), PT (S5) and SCG (S6) in order.